Repercussões clínicas de indivíduos expostos à fumaça tóxica e níveis de cianeto - Stangherlin, Micheli Limana (2019)
The aim of this study was to assess the clinical repercussions of exposition to cyanide in survivors of the fire incident which occurred in Santa Maria, in January 2013. A retrospective, cross-sectional and descriptive study of the survivors of the fire on January 27 2013 who had a cyanide dosage analysis. The sample was obtained from the data base of the CIAVA pneumology ambulatory, at HUSM. The individuals who exposed themselves to the smoke and had a cyanide dosage analysis were included in this study. Those who did not have cyanide dosage analysis or who were not patients of the ambulatory were excluded. An assessment was made of their clinical, demographical and laboratorial data which were later correlated to the level of blood cyanide. Forty five patients were assessed out of a bank of 350. The average age was of 22.6 years old (ranging from 18 to 38 years old), 25 female individuals, 20 male and only 4 had smoking habits. 4 had been previously diagnosed with ashtma and 21 with rhinitis. The smoke exposition time was in average 5 minutes, ranging from 1 to 90 minutes. All individuals were hospitalized for an average of 12 days. Half the patients was admitted into intensive care units with need for ventilatory prosthesis through an average period of 6.8 days. The most frequent initial symptom was coughing (93%), followed by dyspnea (75%), dysphonia (70.5%), sore throat (68%), sputum (65.9%), sensation of thoracic oppression and loss of consciousness in 25 cases each (56.8%) and wheezing (45.5%). 8 patients displayed cyanide levels above 0.1 mcg/ml. A significant association was present between the levels of cyanide and headache (p=0.0037) as well as borderline correlation with oxygen saturation (p=0.05). Manifestations of toxicity by cyanide are very variable, going from mental confusion to cardiac arrest. Our study agrees the previous findings in medical literature that headache is a symptom of cyanide poisoning.